2004
DOI: 10.1177/10442073040150020201
|View full text |Cite
|
Sign up to set email alerts
|

The Educational Inclusion of Disaffected Secondary School Students

Abstract: The government of the United Kingdom has two top educational policy priorities: ensuring that education is as socially inclusive as possible within mainstream schools and raising students' educational attainment standards. In this study, the author explores a continuing tension between government aspirations as represented by the government's policy concerning the education of disaffected and frequently disruptive students (macro level) and an educational provision intended to address these students' needs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Prater (1992) suggested that teachers should create a classroom climate where they spend as little time as possible correcting students' behavior problems by using preventive strategies to decrease unwanted student behavior while positively impacting learning by increasing student time-on-task. Wakefield (2004) concluded that an important step for the teacher to take in order to increase timeon-task is to modify the curriculum to ensure that students see it as relevant to their lives. Also, researchers have found that the type of task assigned by the teacher impacted the amount of time students exhibited on-task behavior.…”
Section: Time-on-taskmentioning
confidence: 98%
“…Prater (1992) suggested that teachers should create a classroom climate where they spend as little time as possible correcting students' behavior problems by using preventive strategies to decrease unwanted student behavior while positively impacting learning by increasing student time-on-task. Wakefield (2004) concluded that an important step for the teacher to take in order to increase timeon-task is to modify the curriculum to ensure that students see it as relevant to their lives. Also, researchers have found that the type of task assigned by the teacher impacted the amount of time students exhibited on-task behavior.…”
Section: Time-on-taskmentioning
confidence: 98%
“…Prater (1992) suggested that teachers should create a classroom climate where they spend as little time as possible correcting students' behavior problems by using preventive strategies to decrease unwanted student behavior, while positively impacting learning by increasing student time-on-task. Wakefield (2004) concluded that an important step for the teacher to take to increase time-on-task is to modify the curriculum to ensure that students see it as relevant to their lives. In addition, researchers have found that the type of task assigned by the teacher impacted the amount of time students exhibited on-task behavior.…”
Section: Time-on-taskmentioning
confidence: 99%